2017
DOI: 10.1002/chem.201702019
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Chiral BINOL‐Derived Phosphoric Acid Catalysts: General Model To Identify Steric Features Essential for Enantioselectivity

Abstract: Choosing the optimal catalyst for a new transformation is challenging because the ideal molecular requirements of the catalyst for one reaction do not always simply translate to another. Large groups at the 3,3′ positions of the binaphthol rings are important for efficient stereoinduction but if they are too large this can lead to unusual or poor results. By applying a quantitative steric assessment of the substituents at the 3,3′ positions of the binaphthol ring, we have systematically studied the effect of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 122 publications
4
61
0
2
Order By: Relevance
“…31 Also, other groups investigated the inuence of different 3,3 0 -substituents of CPAs in several reactions regarding the occurring transition states, the structural differences and/or the enantioselectivity by theoretical methods. [32][33][34][35][36][37][38][39][40] Nevertheless, our recent NMR study about the inuence of 3,3 0 substituents on the structures and populations of binary CPA/ imine complexes revealed a signicant deviation of experimental populations compared to those calculated with the standard theoretical methods applied to these systems. 41 In general, experimental insight into the structures involved in Brønsted acid catalysis is very rare.…”
Section: Introductionmentioning
confidence: 89%
“…31 Also, other groups investigated the inuence of different 3,3 0 -substituents of CPAs in several reactions regarding the occurring transition states, the structural differences and/or the enantioselectivity by theoretical methods. [32][33][34][35][36][37][38][39][40] Nevertheless, our recent NMR study about the inuence of 3,3 0 substituents on the structures and populations of binary CPA/ imine complexes revealed a signicant deviation of experimental populations compared to those calculated with the standard theoretical methods applied to these systems. 41 In general, experimental insight into the structures involved in Brønsted acid catalysis is very rare.…”
Section: Introductionmentioning
confidence: 89%
“…When N-methyl substitutedi ndole 9o was used, the reactionwas sluggish and the resulting stereoselectivity was poor (Scheme 2), suggesting that the hydrogen bond, C 8 H 6 NH···O=P( 1.60 and 1.61 ,r espectively)i si mportant for stabilizing the TSs. [17] Analysiso ft he TS minor geometry revealed that the steric repulsion between one of the bulky substituents of the catalyst and the dibenzyl phosphonate moiety of the substrate are key factors that destabilize TS minor ,c onsistent with the experimental resultst hat substrates bearing the more bulky phosphonate exhibited bettere nantioselectivity (Table 1, entries 1-3). The DDG°between TS major andT S minor was 0.98 kcal mol À1 at the wB97x-D/6-311 + G**//B3LYP/6-31G** level of theory,c orresponding to 67 % ee at 27 8C; this is in good agreement with the experimental results (Table 1, entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the model proposed by Reid and Goodman, [15] the facial selectivity (Re face of the indole and Si face of the diene) can be rationalized by the chiral environment provided by the tethering phosphoric acid, as proposed in Scheme 2. On the basis of the model proposed by Reid and Goodman, [15] the facial selectivity (Re face of the indole and Si face of the diene) can be rationalized by the chiral environment provided by the tethering phosphoric acid, as proposed in Scheme 2.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Themechanism of the cycloaddition is assumed to initially involve loss of H 2 Of rom 1 to generate an ion pair between the newly formed indolium and the chiral phosphate.I nt he meantime,h ydrogen bonding between the dienecarbamate NH group and the Lewis basic phosphoryl oxygen atom ensures ah ighly organized transition state in the enantiodetermining step (Scheme 2). On the basis of the model proposed by Reid and Goodman, [15] the facial selectivity (Re face of the indole and Si face of the diene) can be rationalized by the chiral environment provided by the tethering phosphoric acid, as proposed in Scheme 2. Taking into account the reported conformations of cyclohepta-1,4-dienes [16] and that of exotine natural products (solution and solid-state conformation), [2a] we hypothesize that abent boatlike conformation is adopted in the ring-closing step to afford the all-cis product as the major isomer.Inthe absence of an R 1 group (products 3fand 3g), facile rotation around the C1ÀC2 bond would bring the aromatic substituent into am ore favorable equatorial position, leading to lower diastereoselectivity (see the Supporting Information).…”
Section: Angewandte Chemiementioning
confidence: 99%